The case of the fire inside - Allison, John, 1976- (Allison, John, 1976- Bad machinery, 2016)
It's a new year and Sonny meets a mysterious new girl who seems to have climbed out of the sea itself, while Mildred falls for the bad boy of Saturday detention.